Designing quiz game with multimedia elements as learning object - Raoof, Amin (2013)
Throughout the 1980s and 1990s, the concept of multimedia took on a new meaning, as the capabilities of satellites, computers, audio and video converged to create new media with enormous potential. Combined with the advances in hardware and software, these technologies were able to provide enhanced learning facility, with attention to the specific needs of individual users. Knowledge is going deeper and deeper daily, there are many learning methods developed to catch this huge cloud of knowledge. Each of them are using some senses to make connection with user, reading a book, watching a video and listening to a podcast are examples of them. multimedia can stimulate more than one sense at a time, and in doing so, may be more attention-getting and attention-holding. Presently, traditional learning systems have resulted in a mismatch between what is taught to the user and what the industry needs. As such, many institutions are moving towards problem-based learning as a solution to producing graduates who are creative, can think critically and analytically, and are able to solve problems. Multimedia technology is an innovative learning system. In this project, using multimedia technology in a quiz based learning environment by using multimedia elements, is focused. Based on the analysis of this project, a Quiz-based Learning System is designed and developed. This quiz-based system is consist of a number of technologies that is used in order to produce a full working system. It is revealed, that using of multimedia elements in this quiz-based system has improved the learning ability significantly.